Peer-to-peer lending (P2P) as disruptive, but complementary in Covid-19 exogenous shock - Kohardinata, Cliff; Suhardianto, Novrys; Tjahjadi, Bambang (Business: Theory and Practice, 2024)
The purpose of this study is to examine the effect of P2P lending on bank credit in each type/segment of banking credit consisting of working capital credit, investment credit, and consumer credit in the period before and during the occurrence of the Covid-19 exogenous shock. Examining the effect of P2P lending on various types of bank loans is important because there is no conclusive evidence of whether P2P lending substitutes or complements various conventional bank loans. The Covid-19 pandemic impairs the income of many people and accelerates the use of digital technology in most daily activities including banking. Due to economic contraction during the outbreak, the government requires banks to relax the loan covenants. Therefore, P2P lending that provides flexibility might complement bank loans during the Covid-19 pandemic. The test in this study uses panel regression and is carried out by separating the period before (July 2019–March 2020), and during (July 2020–March 2021) the Covid-19 pandemic. The results show that P2P lending was disruptive for bank loans before the pandemic and turned to be complementary during the pandemic, it might be due to P2P lending flexibility complementing the bank credit relaxation during the pandemic.